ADAPTASI DHARMIKA DALAM BERAGAMA HINDU - Rahayu, Ni Wayan Sri; ., Sugiarti (STAH Dharma Sentana Sulawesi Tengah, 2024)
Abstract Religious conversion is certainly not a new phenomenon in people's lives, this is also the case with people in Toili District, Banggai Regency, Central Sulawesi Province. However, what is very interesting to reveal is related to how conversion actors can carry out the adaptation process to the new environment. Therefore, this research tries to reveal 1) What is the adaptation process of Dharmikas? (2) What obstacles do Dharmikas face in the adaptation process? (3) The efforts made by Dharmikas in facing obstacles to adapting. The results of the research are that there are two adaptation processes carried out by Dharmikas, namely conformity adaptation or the adaptation process by agreeing to cultural goals as well as ways to achieve cultural goals. The second is adaptation by taking a role in the community, either participating in the activities of the Service Banjar or Traditional Banjar. The obstacles faced by Dharmikas in building adaptation are the lack of acceptance of Dharmikas in their husband's family and secondly, namely the lack of guidance specifically carried out by village leaders or Hindu institutions in developing and providing understanding to Dharmikas regarding Hindu teachings. The efforts made by the Dharmikas in facing obstacles in building adaptation include strengthening their commitment to remaining on the path of Hindu Dharma by always asking figures or community members who are considered to understand Hindu teachings and building good relationships with neighbors.